Asphalt Binder Testing at Low Temperature: Three-Point Bending Beam Test in Dynamic Shear Rheometer - Kim, Yun Su; Büchner, Johannes; Wistuba, Michael P.; Agudo, José Rodríguez; Rochlani, Mrinali; Schäffler, Michael (Frontiers in Materials, 2022)
A novel Three-Point Bending Beam Test (3-PBT) using a Dynamic Shear Rheometer (DSR) with linear drive motor is introduced for testing asphalt binder at low temperature conditions. This 3-PBT in DSR can be used as surrogate for Bending Beam Rheometer (BBR) tests. Advantages in comparison to BBR are that (i) 3-PBT works without harmful cooling medium ethanol, (ii) the amount of asphalt binder for testing is significantly lower (using material equivalent of 10% of BBR tests), (iii) a silicone rubber mold is used for specimen preparation instead of standard aluminum mold for BBR tests, which makes handling easier, and (iv) the loading protocol is more practical without applying contact load manually. The novel 3-PBT in DSR is presented with respect to preparation, installation, and conditioning of specimens, as well as to the loading protocol. Tests were conducted at temperatures of −10, −16, and −20°C. For the purpose of comparison to BBR tests, and of identifying most suitable testing conditions from alternative setups, a test series was run including 9 different asphalt binders. As to BBR tests, two different cooling media were used, i.e., ethanol and air. Finally, all test results obtained from DSR and BBR tests were analyzed in view of precision and correlation. DSR results correlated well with BBR results, while precision of 3-PBT in DSR was found to be satisfying.